التهديد الامريكي والتحدي الجيو سياسي الايراني - ضحى لعيبي ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The United States of America devoted its great interest in how to limit Iran's continuation of its nuclear program, so its continuous threats that Iran met with the geo-political challenge and continuation even after its withdrawal from the (5 + 1)agreement signed in 2015 in Vienna, and to demonstrate the importance of Iran's geopolitical dimension in enriching enrichment. Uranium has many military and civilian uses and its political effects toward off potential danger and confront future threats from superpowers. This wasevident in the findings of the research that Iran's geopolitical power after 1979 constitutes a threat point to Israel, and that US President Donald Trump's goal is to disarm it in order to create political stability in the Middle East, according to his claim.key words : The nuclear program, the Vienna Agreement (5 + 1), the geopolitical dimensions, the US strategy, uranium enrichment.